Mihin työelämä on menossa? Tutkimuksen näkökulmia - Heiskanen, Tuula; Syvänen, Sirpa; Rissanen, Tapio (Tampere University Press, 2019)
In this edited book, the authors seek answers to the question "What is the future of working life?" with research-based approaches. The state of working life and its changes and development are affected by many factors starting from global phenomena to workplace level events, actions and procedures. The book examines working life trends on multiple levels covering structural development paths, the role of labor policy, organizational practices and subjective experiences of individuals. Working life research produces valuable information which is beneficial both at workplace level and at the use of decision-makers who regulate working life matters.